Evaluation of Lymphatic and Vascular Invasion in Relation to Clinicopathological Factors and Treatment Outcome in Oral Cavity Squamous Cell Carcinoma. Issue 43 (October 2015) - Adel, Mohamad; Kao, Huang-Kai; Hsu, Cheng-Lung; Huang, Jung-Ju; Lee, Li-Yu; Huang, Yenlin; Browne, Timothy; Tsang, Ngan-Ming; Chang, Yu-Liang; Chang, Kai-Ping
Abstract : Abstract: This study evaluated the associations between lymphatic and vascular invasion of oral cavity squamous cell carcinoma (OSCC) and clinicopathological manifestations, as well as their impact on patient outcomes after treatment. In total, 571 patients with primary OSCC who underwent surgery with or without adjuvant therapy were enrolled. Lymphatic and vascular invasion were found in 28 (5%) and 16 (3%) patients, respectively. Significant associations were found between lymphatic and vascular invasion and overall stage ( P  < 0.001 and P  = 0.020, respectively), tumor stage ( P  = 0.009 and P  = 0.025, respectively), nodal metastasis (both P  < 0.001), extracapsular spread (both P  < 0.001), perineural invasion (both P  < 0.001), bone invasion ( P  = 0.004 and P  = 0.001, respectively), depth of invasion ( P  < 0.001 and P  = 0.001, respectively), and pathologic differentiation ( P  = 0.002 and P  < 0.001, respectively). In the analysis of adverse events during follow-up, neither lymphatic nor vascular invasion was statistically associated with local recurrence, neck recurrence, and distant metastasis. Although lymphatic invasion exhibited significant associations with poorer overall survival ( P  < 0.001), disease-specific survival ( P  < 0.001), and disease-free survival ( P  = 0.01), it was not demonstrated to be an independent prognostic factor in all multivariate analyses. Although both lymphatic and vascular invasion are associated with many clinicopathological manifestations, neither affects the occurrence of locoregional recurrence and distant metastasis in patients with OSCC after treatment.